If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 29 = y + 25 Reorder the terms: 29 + 5y = y + 25 Reorder the terms: 29 + 5y = 25 + y Solving 29 + 5y = 25 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 29 + 5y + -1y = 25 + y + -1y Combine like terms: 5y + -1y = 4y 29 + 4y = 25 + y + -1y Combine like terms: y + -1y = 0 29 + 4y = 25 + 0 29 + 4y = 25 Add '-29' to each side of the equation. 29 + -29 + 4y = 25 + -29 Combine like terms: 29 + -29 = 0 0 + 4y = 25 + -29 4y = 25 + -29 Combine like terms: 25 + -29 = -4 4y = -4 Divide each side by '4'. y = -1 Simplifying y = -1
| 3x+4x=8x-10 | | 12=k-7 | | 6x-5=4x+17 | | f-32*0.55=4 | | 9=w+2 | | 0=x^2-2x-8 | | 8(c-2)=7(4+c) | | 15=r-7 | | 2y-1=4y-5 | | m-4=10 | | 3t-15=2t+10 | | 110-32*0.55=c | | f-2=4 | | 19-4x=-1 | | c+3=9 | | y=x^2-2x-8 | | -5y-1=-4y-7 | | 2=h-8 | | p-7=8 | | y+5=14 | | 2x+5=57 | | 8-5(12x+8)= | | 3x=6-2y | | 2c+2+5c= | | 6x=70 | | 4x^4-4x^2+1=0 | | xy+(y)(y)=-5 | | m/5+4=18 | | x-2y=-3 | | 12-60=3-k | | 19x+3y=23 | | 27.48=p-28 |